2003
DOI: 10.1038/sj.ijo.0802416
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy and diastolic function in physically well trained and in obese men

Abstract: OBJECTIVE:The aim of the present study was to compare cardiac hypertrophy and diastolic function in extremely obese male patients and physically active adult male subjects of similar age (means 43.0-43.4 y). DESIGN: Data of male patients referred to our hospital ward in order to reduce their body weight (BW) were compared with those of physically active and nonactive healthy males. SUBJECTS: The groups contained 21-24 male subjects, very active and moderately active subjects taking part in regular competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Higher peak velocity of atrial wave and lower average E/A ratio in obese subjects suggested impaired left ventricular diastolic function. Similar observations were published by Sido et al 23 in the group of slightly older men (mean age 43 years), where E/A ratio was lower in extremely obese men than in age-matched physically active people. The comparison of tissue Doppler velocities revealed a biventricular impairment of systolic and early diastolic function in patients with severe obesity.…”
Section: Discussionsupporting
confidence: 89%
“…Higher peak velocity of atrial wave and lower average E/A ratio in obese subjects suggested impaired left ventricular diastolic function. Similar observations were published by Sido et al 23 in the group of slightly older men (mean age 43 years), where E/A ratio was lower in extremely obese men than in age-matched physically active people. The comparison of tissue Doppler velocities revealed a biventricular impairment of systolic and early diastolic function in patients with severe obesity.…”
Section: Discussionsupporting
confidence: 89%
“…34,87,143 Specifically, it has been used to assess morphological and functional changes in the myocardium during isometric exercise 12 and endurance training, 38,42,112 as well as comparison of these changes between different populations (athletes, 96 nonathletes, 96 and obese individuals 116 ) and as a function of age. 97 In addition to the above applications, m-mode USI has been used to assess pulmonary function, specifically diaphragm excursion, motility, and paralysis.…”
Section: M-mode Ultrasound Imagingmentioning
confidence: 99%